Quantification of Myocardial Dosimetry and Glucose Metabolism Using a 17-Segment Model of the Left Ventricle in Esophageal Cancer Patients Receiving Radiotherapy - Sha, Xue; Gong, Guanzhong; Han, Chunlei; Qiu, Qingtao; Yin, Yong (Frontiers in Oncology, 2020)
Objective: Previous studies have shown that increased cardiac uptake of 18F-fluorodeoxyglucose (FDG) from positron emission tomography (PET) may be an indicator of myocardial injury after radiotherapy. The primary objective of this study was to quantify cardiac subvolume dosimetry and 18F- FDG uptake in oncologic PET using a 17-segment model of the left ventricle (LV) and to identify dose limits related to changes in cardiac FDG uptake after radiotherapy (RT). Methods: Twenty-four esophageal cancer (EC) patients who underwent consecutive oncologic 18F-FDG PET/CT scans at baseline and post-RT were enrolled in this study. The radiation dose and the 18F-FDG uptake were quantitatively analyzed based on a 17-segment model. The 18F-FDG uptake and doses to the basal, mid and apical regions, and the changes in the 18F-FDG uptake for different dose ranges were analyzed. Results: A heterogeneous dose distribution was observed, and the basal region received a higher median mean dose (18.36 Gy) than the middle and apical regions (5.30 Gy and 2.21 Gy, respectively). Segments 1, 2, 3 and 4 received the highest doses, all of which were greater than 10 Gy. Three patterns were observed for the myocardial 18F-FDG uptake related to the radiation dose before and after RT: an increase (5 patients), a decrease (13 patients) and no change (6 patients). In the pairing analysis, the 18F-FDG uptake after RT decreased by 28.93% and 12.12% in the low-dose segments (0-10 Gy and 10-20 Gy, respectively) and increased by 7.24% in the high-dose segments (20-30 Gy). Conclusions: The RT dose varies substantially within LV segments in patients receiving thoracic EC RT. Increased 18F-FDG uptake in the myocardium after RT was observed for doses above 20 Gy.